Record label marketing - Hutchison, Thomas W. (Focal Press, 2010)
Record Label Marketing offers a comprehensive look at the inner workings of record labels, showing how the record labels connect commercial music with consumers. In the current climate of selling music through both traditional channels and new media, authors Tom Hutchison, Paul Allen and Amy Macy carefully explain the components of the contemporary record label's marketing plan and how it is executed. This new edition is clearly illustrated throughout with figures, tables, graphs, and glossaries, and includes a valuable overview of the music industry. Record Label Marketing has become esse.
Includes bibliographical references and index. - Print version record
Keywords: Music trade; Sound recordings -- Marketing; Sound recording industry; Musique; Industrie; Enregistrements sonores; Industrie; Sound recordings; Marketing; Tonträgerindustrie; Tonträger; Vermarktung; Grammofonindustri; Musikbranschen; Marknadsföring; dissertations; Academic theses; Thèses et écrits académiques